Epic - Wedge, Chris, 1958-; Forte, Lori; Davis, Jerry; Joyce, William, 1957-; Hart, James V.; Shere, Dan; Astle, Tom J.; Ember, Matt; Farrell, Colin, 1976-; Hutcherson, Josh; Seyfried, Amanda; Waltz, Christoph, 1956-; et al. (Beverly Hills, Calif. Twentieth Century Fox Home Entertainment, 2013)
The story of an ongoing battle deep in the forest between the forces of good and the forces of evil. When a teen age girl finds herself magically transported into this secret universe, she must band together with a rag-tag team of fun and whimsical characters in order to save their world, and also ours.
Originally released as a motion picture in 2013.
Leafmen characters inspired by the book: The Leaf Men and the brave good bugs / by William Joyce.
Extras: Birds, bugs and slugs: forest explorer; Rot rocks; Bugs of camouflage; Theatrical trailer.
Music by Danny Elfman ; production designers, Greg Couch, William Joyce ; art director, Michael Knapp ; edited by Andy Keir ; supervising animators, Galen Tan Chu, Melvin Tsing Chern Tan ; cinematographer, Renato Falcao.
Voices: Colin Farrell, Josh Hutcherson, Amanda Seyfried, Christoph Waltz, Aziz Ansari, Chris O'Dowd, Pitbull, Jason Sudeikis, Steven Tyler, Beyonce Knowles.
Rating: PG; for mild action, some scary images and brief rude language CHV rating: PG.
Keywords: Good and evil -- Juvenile films; Imaginary places -- Juvenile films; Heroes -- Juvenile films; Forest animals -- Juvenile films; Feature films -- United States; United States; DVD-Video discs; Feature films -- Juvenile; Animated films -- Juvenile; Comedy films -- Juvenile; Video recordings for the hearing impaired -- Juvenile; Video recordings for people with visual disabilities -- Juvenile; Action and adventure films; Animated films; Film adaptations; Feature films; Fiction films; Children's films; Juvenile works